Nurturing architecture : shifting conventional architectural approaches towards regenerative architecture - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2016)
Mini Dissertation (MArch(Prof))--University of Pretoria, 2015.